The human hippocampus beyond the cognitive map: evidence from a densely amnesic patient - Banta Lavenex, Pamela A.; Colombo, Françoise; Ribordy Lambert, Farfalla; Lavenex, Pierre (Frontiers in Human Neuroscience, 2014)
We tested a densely amnesic patient (P9), with bilateral hippocampal damage resulting from an autoimmune disorder, and 12 age- and sex-matched controls on a series of memory tasks designed to characterize allocentric spatial learning and memory abilities. We compared P9’s ability to perform spatial memory tasks with her ability to perform non-spatial, color memory tasks. First, P9’s performance was impaired as compared to controls even in the simplest versions of an allocentric spatial memory task, in which she had to find repeatedly over ten trials the same location(s) of one, two or three illuminating foot pad(s) among 23 pads distributed in an open-field arena. In contrast, she performed as well as controls when she had to find repeatedly over ten trials the same one, two or three pad(s) marked by color cue(s), whose locations varied between trials. Second, P9’s performance was severely impaired in working memory tasks, when she had to learn on a trial-unique basis and remember the location(s) or the color(s) of one, two or three pad(s), while performing an interfering task during the one-minute interval separating encoding and retrieval. Without interference during the retention interval of the trial-unique tasks, P9’s performance was partially preserved in the color tasks, whereas it remained severely impaired in the allocentric spatial tasks. Detailed behavioral analyses indicate that P9’s memory representations are more limited than those of controls both in their precision (metric coding) and in the number of items that can be maintained in memory (capacity). These findings are consistent with the theory that the hippocampus contributes to the integration or binding of multiple items, in order to produce high-resolution/high-capacity representations of spatial and non-spatial information in the service of short-term/working and long-term memory.